Organized crime in the United States, 1865-1941 - Allerfeldt, Kristofer (McFarland & Company, Inc., Publishers, 2018)
"Why do Americans alternately celebrate and condemn gangsters, outlaws and corrupt politicians? Why do they immortalize Al Capone while forgetting his far more successful, innovative precursor, Michael Cassius MacDonald? Drawing on historical accounts, the author analyzes the public's understanding of organized crime and questions some of our most deeply held assumptions about crime and its role in society"--